Growing Up : From Baby to Adult - Harris, Nic; Naughton, Diane (NewYork Cambridge University, 2014)
Do you remember being a baby? When are you grown up? Learn how humans and animals grow from babies to adults, and what it means to be an adult in different cultures.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents. Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Keywords: English language; Elementary level